The Effect of E-Recruitment on Company Attractiveness with the Role of Organisational Reputation as a Mediating Variable - M. Ilham Timur Abdillah; Joko Suyono (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2024)
This recruitment process is very important in selecting the right candidates for jobs in the company. Traditional methods such as newspaper and television advertisements have been replaced by electronic recruitment (e-recruitment) systems as a result of technological advances, particularly the Internet. This study looks at how e-recruitment affects an organization's attractiveness from the point of view of prospective employees who use this system to apply for jobs. This study used a quantitative approach and was designed as a survey. A purposive sampling technique was used to select 213 freshmen. Participants were selected based on certain criteria related to the study. The partial least squares (PLS-based) structural equation modeling (SEM) method was used to analyze data collected through an online questionnaire. The results showed that e-recruitment had a major impact on fresh graduates' perceptions of the attractiveness and reputation of the organization. Factors such as e-recruitment content quality, website design, and communication and feedback systems play a major role in shaping these perceptions. The findings help us understand how e-recruitment can increase an organization's attractiveness and how this has practical implications for companies in designing a website.